Structuring of 2D photonic crystal on InP membranes as polarizing element for optical MEMS based sensor systems - Zamora, R.; Kusserow, T.; Wulf, M.; Kanwar, K.; Witzigmann, Bernd; Hillmer, H. (INSS 2010 - 7th International Conference on Networked Sensing Systems, 2010)
Narrow band Fabry-Ṕrot MEMS filters are investigated for the integration in optical fiber sensor networks. We present a technological process to implement a 2D photonic crystal (PhC) structure on an InP membrane, in order to provide an InP/air-gap Fabry-Ṕrot filter with polarization selectivity. The capabilities and limitations of Focused Ion Beam (FIB) lithography combined with Reactive Ion Etching (RIE) are investigated to fabricate the PhC structure. Special focus is given to the etching rate of the required hard mask, utilized in the FIB lithography, to determine the optimal thickness to produce high quality structures. Additionally, the mechanical properties of the PhC membrane and the influence on the basic filter structure are investigated. © 2010 IEEE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Fabry-Perot filter; FIB lithography; Fiber based sensor networks; Photonic crystals; Polarization selectivity; RIE